E-WASTE MANAGEMENT: A BIBLIOMETRIC ANALYSIS FROM 2019 TO 2025 - Abdullah, Che Wan Noorakma; Ariff, Hambali Arep; Sultan, Al Amin Mohamed (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
The current study is an elaborate bibliometric report on trends in international research on electronic waste (e-waste) management from 2019 to 2025 using data extracted from the Scopus database. The objective is to evaluate publication trends, identify influential authors, institutions, and countries, and explore thematic developments through co-occurrence, co-authorship, and citation network analyses. The analysis includes 3,317 publications focused on key environmental, engineering, and technological subject areas. Results demonstrated a substantial upward trajectory in research output, with a maximum of publications in 2024, because the problem of e-waste is being increasingly considered by researchers. India, China, and the United States emerge as leading contributors, while the Chinese Academy of Sciences, as well as the Ministry of Education of China, dominate institutional output. Keyword co-occurrence analysis highlights major research clusters, including metal recovery, environmental risks, policy implementation, and technological innovations such as Internet of Things (IoT) and Artificial Intelligence (AI). Country collaboration and co-authorship networks underscore strong research linkages in Asia and Europe, although disparities in global participation persist. This work highlights the relevance of further interdisciplinary and international collaboration to resolve the growing problem of e-waste. It offers researchers, policymakers, and stakeholders findings that are of great relevance to enhancing sustainable waste management practices.